Sequenciamento de isolados da raça 65 de Colletotrichum lindemuthianum utilizando as regiões ITS - Coêlho, Marcela (2014)
Anthracnose, caused by Colletotrichum lindemuthianum (Sacc and Magnus) Briosi and Cavara, is one of the most severe fungal diseases that attack common bean. An effective method to control anthracnose in common bean is to use resistant cultivars, but the emergence of new physiological races of C. lindemuthianum is a challenge to implement this strategy. Among the C. lindemuthianum races, the race 65 stands out for having been identified in several countries, including Brazil. In addition, there are several records that isolates of race 65 from different locations, present genetic variability. One of the techniques to study genetic variability in pathogens involves the sequencing of ITS regions (Internal Transcribed Spacer) of the ribosomal DNA (rDNA). Thus, the objective of this study was to characterize isolates of C. lindemuthianum race 65 from different regions of Brazil, through the sequencing of ITS regions. A total of 17 isolates of race 65, collected in the states of Mato Grosso, Minas Gerais, Paraná, Santa Catarina and São Paulo were studied. The results revealed the existence of high genetic variability among and within the race 65. The sequence analysis of 17 isolates of race 65 showed the presence of 11 SNPs (single nucleotide polymorphism) in the ITS regions. In the ITS1 region ware identified the presence of 6 SNPs, while in the ITS2, 5 SNPs were identified. The largest genetic dissimilarity was observed among isolates 10 and 11 from Santa Catarina state and among isolates 3 and 11 from Mato Grosso and Santa Catarina states, respectively, which value was 0.772. On the other hand, the most similar isolates were 2 and 7 (genetic distance of 0.002) collected in Mato Grosso and Santa Catarina states, respectively. The phylogenetic tree obtained from the ITS1 and ITS2 sequences, revealed the presence of two well-defined groups (Group I and II). Group I consisted of 2 isolates from Santa Catarina and 1 isolate each of the states Mato Grosso, São Paulo and Paraná. Group II was composed of two subgroups, one being formed by 6 isolates from Santa Catarina, 3 isolates from São Paulo, 2 from Mato Grosso and 1 isolated from Minas Gerais, while the second subgroup consisted of 1 isolate from Santa Catarina.